How does habit strength affect reactions to warning labels? evidence from Chinese consumers' choices of carbonated beverages. - Yulian Ding; Yue Yang; Yangyang Sun; Kevin Chen; Lianfeng Hu (PLoS ONE)
Effectively regulating the excessive consumption of sugar-sweetened beverages (SSBs) has been an important task for public health authorities around the world. The rapid increase in SSB consumption in China necessitates robust regulations. This study employed a choice experiment to simulate the market scenario in which a text warning label was presented on SSBs. We draw a sample of 1200 participants from five major cities across China to analyze the warning label's effectiveness in reducing urban consumers' purchases of SSBs, with a particular emphasis on how an individual's habit strength affects their reaction to the warning label. Our analysis unveiled varying levels of habit strength among respondents: 35.33% showed weak habits, 56.25% displayed moderate habits, and 8.42% demonstrated strong habits. The random parameters logit model results showed a significant overall decrease in SSB purchases when a warning label was present, indicated by a significant negative coefficient associated with the label. However, when examining the impact of warning labels across different habit strengths, a significant effect was observed only in the moderate habit group. Furthermore, within this group, the warning label was more effective for those with correct health knowledge and who were not overweight or obese.